The influence of reinforcement strengthening on seismic response and index correlation for high arch dams by endurance time analysis method. (August 2021) - Xu, Qiang; Zhang, Tianran; Chen, Jianyun; Li, Jing; Li, Chengyu
Highlights: The correlation of response indices under various seismic intensities is analyzed. The effect of reinforcement on the response index correlation is discussed. The effect of reinforcement on a dam's damage process is explored. Abstract: This study aims to explore the correlation between the seismic response indices of high arch dam with and without cantilever reinforcement strengthening. The nonlinear dynamic responses of the 289-m-high Baihetan dam located in southwestern China, to three-component endurance time acceleration histories are investigated. The dynamic responses, including damage distribution, displacement, and joint opening, are statistically analyzed. Furthermore, the proposed seismic response indices, including the global and local damage volume ratios, the average joint opening, and the displacement of the crown cantilever are studied. By comparing the seismic response indices with and without reinforcement, the effects of cantilever reinforcement on the changing trend and range of the seismic response indices are discussed. Subsequently, the correlation curves of the seismic response indices are demonstrated, and the correlation calculated with reinforcement between the seismic response indices is identified. To provide a better correlation analysis, the correlation of each seismic response index is classified. Numerical results show that the changing trend of correlation of the damage indices v. the upstream displacement is different from that of the damage indices v. the downstream displacement. When the peak ground acceleration is approximately 0.5 g, cantilever reinforcement has a significant effect on limiting damage development in the middle-upper part of the downstream face. However, cantilever reinforcement has a limited effect on the correlation between each seismic response index under different peak ground accelerations.